A roadmap for personalized medicine: the findings of the IC2PerMed project - Beccia, Flavia; Causio, Francesco Andrea; Di Marcantonio, Marzia; Hoxhaj, Ilda; Cadeddu, Chiara; Campagno, Melissa; Schleicher, Lena; Fotino, Carmen; Tauchert, Maike; Lomazzi, Marta; Wang, Lili; Wang, Wenya; et al. (Frontiers in Medicine, 2025)
IntroductionPersonalized Medicine (PM) tailors prevention and treatment to individuals based on their unique characteristics. It has the potential to improve health outcomes and healthcare sustainability by optimizing resource allocation. Both the European Union (EU) and China have prioritized PM in their health strategies. The IC2PerMed project was established to foster collaboration between the EU and China by developing a joint PM roadmap.MethodsTo assess the state of PM in the EU and China, the project conducted a comprehensive mapping of relevant policies, programs, funding mechanisms, and health ecosystems. Additionally, three Delphi surveys were carried out, identifying 65 priorities, which were synthesized into a set of strategic actions.ResultsThe main output of the project is a joint roadmap for implementing PM in the EU and China. The roadmap promotes best practice exchange and addresses potential barriers to PM adoption. It outlines structural actions including enhancing health literacy, fostering intersectoral and international collaboration, ongoing review of emerging technologies, and facilitating innovation market entry through needs assessment and Health Technology Assessment. Key enablers such as data interoperability and shared standards are highlighted, along with ethical, social, and regulatory considerations that are universally relevant to PM implementation.DiscussionA shared action plan can guide health policy and help policymakers understand the interconnection between healthcare, the economy, and society. By supporting international projects and investing in research and innovation, stakeholders can advance global healthcare.